Silicon surface passivation by aluminium oxide studied with electron energy loss spectroscopy. Issue 11 (14th August 2013) - Hoex, Bram; Bosman, Michel; Nandakumar, Naomi; Kessels, W. M. M.
Abstract The origin behind crystalline silicon surface passivation by Al2O3 films is studied in detail by means of spatially‐resolved electron energy loss spectroscopy. The bonding configurations of Al and O are studied in as‐deposited and annealed Al2O3 films grown on c‐Si substrates by plasma‐assisted and thermal atomic layer deposition. The results confirm the presence of an interfacial SiO2‐like film and demonstrate changes in the ratio between tetrahedrally and octahedrally coordinated Al in the films after annealing. These observations reveal the underlying origin of c‐Si surface passivation by Al2O3. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)